Association Equilibrium of the HIV-1 Capsid Protein in a Crowded Medium Reveals that Hexamerization during Capsid Assembly Requires a Functional C-Domain Dimerization Interface - Bocanegra, Rebeca (The Biophysical Society, 2013)
Polymerization of the intact capsid protein (CA) of HIV-1 into mature capsidlike particles at physiological ionic strength in vitro requires macromolecularly crowded conditions that approach those inside the virion, where the mature capsid is assembled in vivo. The capsid is organized as a hexameric lattice. CA subunits in each hexamer are connected through interfaces that involve the CA N-terminal domain (NTD); pairs of CA subunits belonging to different hexamers are connected through a different interface that involves the C-terminal domain (CTD). At physiological ionic strength in noncrowded conditions, CA subunits homodimerize through this CTD-CTD interface, but do not hexamerize through the other interfaces (those involving the NTD). Here we have investigated whether macromolecular crowding conditions are able to promote hexamerization of the isolated NTD and/or full-length CA (with an inactive CTD-CTD interface to prevent polymerization). The oligomerization state of the proteins was determined using analytical ultracentrifugation in the absence or presence of high concentrations of an inert macromolecular crowding agent. Under the same conditions that promoted efficient assembly of intact CA dimers, neither NTD nor CA with an inactive CTD-CTD interface showed any tendency to form hexamers or any other oligomer. This inability to hexamerize was observed even in macromolecularly crowded conditions. The results indicate that a functional CTD-CTD interface is strictly required for hexamerization of HIV-1 CA through the other interfaces. Together with previous results, these observations suggest that establishment of NTD-CTD interactions involved in CA hexamerization during mature HIV-1 capsid assembly requires a homodimerization-dependent conformational switching of CTD.